Finding Grant Opportunities to Support County Extension Programs - Amy Harder; Alexa Lamm; Sebastian Galindo (EDIS, 2012)
This 3-page fact sheet presents information about where to look for grant opportunities, what to look for when reviewing grant opportunities, and how to determine if the opportunity fits your idea. Written by Amy Harder, Alexa Lamm, and Sebastian Galindo, and published by the UF Department of Agricultural Education and Communication, December 2012.